First record of Huarpea wagneriella (Hymenoptera: Sapygidae) as a cleptoparasite of large carpenter bees (Hymenoptera: Apidae, Xylocopinae) - Lucia, Mariano (2016)
The species Huarpea wagneriella (Hymenoptera: Sapygidae), a cleptoparasite of nests of bees of the genera Xylocopa Latreille and Megachile Latreille (Hymenoptera: Apoidea), is reported for the first time as a cleptoparasite of Xylocopa ciliata Burmeister (Hymenoptera: Apidae) in Buenos Aires, Argentina. Biological notes on species of Xylocopa and a morphological characterization of Huarpea are given.